Small statehood and the Commonwealth reconsidered (Carfax Pub. AbingdonGB, 1997)
Provides an analysis of complex issues concerning small states' security and development. Provides also a series of action points to counteract small states' vulnerability.
Presented to the delegates by The Round Table